Black soldier fly Hermetia illucens Linnaeus (Insecta: Diptera: Stratiomyidae) - Joseph W. Diclaro II; Phillip E. Kaufman (EDIS)
EENY-461, a 4-page illustrated fact sheet by Joseph W. Diclaro II and Phillip E. Kaufman, is part of the Featured Creatures collection. It describes this sleek looking fly often mistaken for a wasp — synonymy, distribution, description and life cycle, and economic importance. Includes selected references. Published by the UF Department of Entomology and Nematology, June 2009.